Study the association of the cardiac risk indices and high sensitive C-reactive protein for Type 2 diabetes patients in tertiary care hospital, Puducherry - Suresh Pichandi; Janakiraman P; Muraliswaran P; Prabhu G (Asian Journal of Medical Sciences, 2022)
Background: Diabetes mellitus (DM) is a metabolic disorder with hyperglycemia. Dyslipidemia associated with DM patient and contributing to atherovascular events and increases the likelihood of cardiovascular disease (CVD) in future. Measurement of inflammatory marker like hs-CRP will improve the prediction of the risk of these events. This study aimed to assess the cardiac risk indices and determine their association with hs-CRP in diabetic patients. Aims and Objectives: This study is aimed to assess the association of the cardiac risk indices and hs-CRP in diabetic patients. Materials and Methods: This study included each 125 subjects of Type 2 diabetic patients and healthy control. The anthropometric parameters (BMI and WHR) and blood parameters such as fasting glucose, glycosylated hemoglobin (HbA1c), lipid profile (total cholesterol, TGL, HDL, and LDL), hs-CRP, and microalbumin were measured. Cardiac risk indices calculated from lipid profile. Results: High cardiac risk indices were observed in diabetic subjects. The cardiac risk indices were showed that significant positive correlation with BMI, fasting sugar, HbA1c, total cholesterol, TGL, LDL and HDL shows negative correlation. Furthermore, hs-CRP and microalbumin showed significant positive correlation with cardiac risk indices in Type 2 DM patients. Conclusion: The increased in values of cardiac risk indices in diabetic patients shows increasing the susceptibility of CVD in these patients in future. The correlation of indices values with hs-CRP (inflammatory marker)shows the direct association of inflammation with CVD risks in Type 2 DM patients. Screening of these indices among diabetic patients will help the propensity of future development of CVD which can be arrested by encouragement of healthy lifestyle.